Türk Hukukunda işkence cürmü -TCK.nun 4449 sayılı kanunla değişik 243.maddesi- - Üzülmez, İlhan (My University, 2001)
Türk Hukukunda İşkence Cürmü -TCK.nun 4449 sayılı Kanunla Değişik 243. Maddesi- başlıklı bu çalışmada ağır insan hakları ihlallerinden olan, bir kişiye işkence etmek, zalimane, gayriinsai ve haysiyet kırıcı muamelelerde bulunmak yasağının ihlalini cezalandıran TCK.nun 4449 sayılı Kanunla değişik 243. maddesi incelenmiştir. Çalışma üç bölümden oluşmaktadır: İlk bölümde, işkencenin tanımı, hukuki niteliği, işkence suç kavramı, mukayeseli hukuklarda düzenleniş şekli ele alınmış ve işkencenin batı hukukunda ve Türk hukukundaki tarihi gelişimine değinilmiştir. İkinci bölümde ise, işkence ceza yargılaması hukuku açısından değerlendirilmiştir. Bu bölümde, ceza yargılamasında geçerli olan maddi gerçeğe ulaşma kuralının anlamı ve işkencenin niçin bu amaca aykırılık oluşturduğu anlatılmıştır. Son bölümde ise, işkence suçunun unsurları incelenmiştir. Bu bölümde, Yargıtay'ın, İnsan Hakları Avrupa Komisyonu ve Mahkemesinin kararlarından faydalanılmış ve bu çerçevede hukuki sorunlara çözümler önerilmiştir.

In this study, named The Torture crime in Turkish Law (The revised article of 243 of Turkish Criminal Law bythe rule no 4449), The 243 article of Crimninal law-revised by the rule no 4449- that penalizes one ofthe most serious human rights spoiling, namely to torture a person, to behave a person in a cruel, unhumanly and contrary to human dignity manner, has been examined. The study is divided into three sections. In the first section the following topics have been analyzed: the definition of torture, its law characteristics, the concept of torture crime, its regulation in comparative laws and its development in Turkish Law and Western Laws. In the second section, the topic has been investigated according to criminal judiciary law. In this section the meaning of the obtaining the concrete reality in criminal judgement and the reasons for the torture crime to be against this principle have been explained. In the last section, the components of the torture crime have been searched. In this section, the decisions of the Yargıtay (Turkish high council for civil judiciary) as well as those of the European Human Rights Council and Court have been used in order to offer some solutions to some judgemental problems.
Keywords: Anayasa ve idare hukuku; Hukuk; Hukuk-Kamu Hukuku